2017
DOI: 10.1016/j.ijheh.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Maternal prenatal blood mercury is not adversely associated with offspring IQ at 8 years provided the mother eats fish: A British prebirth cohort study

Abstract: BackgroundConflicting evidence concerning possible harm from mercury (Hg) in regard to offspring cognition if the woman eats fish has prompted this study to examine evidence from a British pre-birth cohort to investigate the relationship between the two.MethodsPregnant women (median prenatal blood mercury 1.86 μg/L) resident in the study area with delivery between April 1991 and December 1992 were followed up and verbal, performance and total intelligence quotient (IQ) of 2062 offspring were measured at age 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…They represent 24 unique cohorts that met the criteria for inclusion and did not meet criteria for exclusion for this question. Of these 29 studies, seven were conducted in the United States [15,20,22,27,32,34,37]; seven in the United Kingdom [13,14,17,19,35,38,39]; three in Spain [23,31,36]; two in Italy [28,29] three in the Republic of the Seychelles [18,25,26]; and one each in Denmark [21], Norway [40], the Netherlands [33], China [30], Japan [24], the Faroe Islands [16] and another in a consortium of European countries [41]. The sample sizes ranged from 135 [15] to 38,581 mother-child pairs [40] with a median sample size of 498 mother child pairs [24].…”
Section: Question #40 What Is the Relationship Between Maternal Seafmentioning
confidence: 99%
See 1 more Smart Citation
“…They represent 24 unique cohorts that met the criteria for inclusion and did not meet criteria for exclusion for this question. Of these 29 studies, seven were conducted in the United States [15,20,22,27,32,34,37]; seven in the United Kingdom [13,14,17,19,35,38,39]; three in Spain [23,31,36]; two in Italy [28,29] three in the Republic of the Seychelles [18,25,26]; and one each in Denmark [21], Norway [40], the Netherlands [33], China [30], Japan [24], the Faroe Islands [16] and another in a consortium of European countries [41]. The sample sizes ranged from 135 [15] to 38,581 mother-child pairs [40] with a median sample size of 498 mother child pairs [24].…”
Section: Question #40 What Is the Relationship Between Maternal Seafmentioning
confidence: 99%
“…Ten studies reported that the FFQ provided prompts for frequency, e.g. "less than once per week," or "more than once per day" [15,17,19,22,29,31,32,35,37,39]. Two studies reported administering an FFQ during first trimester [31,36].…”
Section: Question #40 What Is the Relationship Between Maternal Seafmentioning
confidence: 99%
“…The role of Hg as a toxicant in sexual reproduction and pregnancy is quite neglected compared with the great attention spent on reports regarding neurotoxicology from this heavy metal. Despite some contradictory evidence, the role of Hg in human reproduction is going to be a major alarming issue . This MiniReview is aimed at analysing the published documentation about the effects of organic and inorganic Hg in human fertility, the outcome of childbirth, congenital abnormalities, loss of pregnancy and menstrual disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Despite some contradictory evidence, the role of Hg in human reproduction is going to be a major alarming issue. [32][33][34][35][36][37] This MiniReview is aimed at analysing the published documentation about the effects of organic and inorganic Hg in human fertility, the outcome of childbirth, congenital abnormalities, loss of pregnancy and menstrual disorders.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in the United Kingdom found that children of mothers who had eaten no seafood but had still been exposed to mercury showed a trend toward lower IQ scores while children of mothers who had eaten seafood and had been exposed to the same levels of mercury experienced gains in IQ [40]. Like the Seychelles and Faroe Islands results when compared against each other, this study suggests that the nutrients in seafood can cause seafood to be beneficial notwithstanding the presence of mercury that could otherwise cause a decline in neurocognitive test results.…”
Section: Considerations About Mercurymentioning
confidence: 99%